2001
DOI: 10.1079/phn2000117
|View full text |Cite
|
Sign up to set email alerts
|

Habitual diet in four populations of African origin: a descriptive paper on nutrient intakes in rural and urban Cameroon, Jamaica and Caribbean migrants in Britain

Abstract: Background: The prevalence of chronic diseases is increasing in West Africa, the Caribbean and its migrants to Britain. This trend may be due to the transition in the habitual diet, with increasing (saturated) fat and decreasing fruit and vegetable intakes, both within and between countries. Objective: We have tested this hypothesis by comparing habitual diet in four Africanorigin populations with a similar genetic background at different stages in this transition. Design: The study populations included subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
6
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 15 publications
5
35
6
1
Order By: Relevance
“…32 Our data refer only to people of Caribbean origin and African descent and not to people of direct West African origin, whose dietary and cultural background are quite different. 33 These issues are discussed elsewhere. 34 In conclusion, the results suggest that PWV is a powerful independent predictor of later mortality across the entire spectrum of glucose tolerance, with or without overt type 2 diabetes.…”
Section: Table 2 Baseline Clinical Characteristics Of the Subjects Bmentioning
confidence: 99%
“…32 Our data refer only to people of Caribbean origin and African descent and not to people of direct West African origin, whose dietary and cultural background are quite different. 33 These issues are discussed elsewhere. 34 In conclusion, the results suggest that PWV is a powerful independent predictor of later mortality across the entire spectrum of glucose tolerance, with or without overt type 2 diabetes.…”
Section: Table 2 Baseline Clinical Characteristics Of the Subjects Bmentioning
confidence: 99%
“…Studies of food consumption and nutritional composition in Black British adults are limited and largely confined to people of Caribbean ancestry (6)(7)(8) . Previous studies have recognised distinct nutritional composition differences between native Caribbean and first-generation migrant Caribbean communities in the UK, suggesting that migration and the processes of acculturation (9) result in increasing intakes of energy, fat and saturated fat (8) ; although when compared with White Europeans, intakes of fat and saturated fat remain significantly lower in UK African-Caribbean adults (6) .…”
mentioning
confidence: 99%
“…Indeed, migration and acculturation are associated with significant changes in dietary patterns (3) . Several studies have shown that migrants adopt the dietary patterns of their new host country, resulting in negative consequences for health (4)(5)(6) . However, the extent of these changes varies with each ethnic group (7) .…”
mentioning
confidence: 99%